Cryptococcal infection causing longitudinal extensive transverse myelitis in an immunocompetent individual: Case report and literature review - Panda, Ashwin Kumar; Hazra, Sourav; Anthony, Aldrin; Kushwaha, Suman (Frontiers in Neurology, 2023)
Cryptococcal CNS infections in immunocompetent individuals are occasionally reported in literature. The spinal manifestations of cryptococcal CNS infections are epidural abscess, chronic arachnoiditis, intramedullary granuloma, myelitis and vasculitis. We report a rare case of CNS cryptococcal infection presenting as a longitudinal extensive transverse myelitis (LETM) in an immunocompetent male. This report highlights cryptococcus as an important etiology among infectious causes in acute LETM patients in-spite of the immunocompetent status of the patient and the utility of CRAG (cryptococcal antigen) for diagnosis in such patients. We also present a literature review of all reported cases of cryptococcal myelitis.